Perbedaan Pengalaman Klinik Mahasiswa Pendidikan Profesi Dokter di Departemen Ilmu Bedah Tiga Rumah Sakit Pendidikan - Marindra Firmansyah (JIMR - Journal of Islamic Medicine Research, 2017)
Introduction: Clinical education of medical faculty UNISMA regularly conducts continuous evaluation of learning components in the clinical rotation. It is important to know the achievement of competence and also to make improvements and development as deemed necessary. The aim of this study was to know and analysed the differences of exposure on clerkship students during their clinical rotation to core cases of competences between three teaching hospitals in the department of surgery and to know their perception about the role of preceptor in three teaching hospitals between three teaching hospitals in the department of surgery. Methods: The study is a descriptive analitic survey, cross sectional of clerkship students FK UNISMA in the Department of Surgery in teaching hospitals. The teaching hospitals are Kanjuruhan Hospital, Mardi Waluyo Hospital and Blambangan Hospital. The level of exposure of cases in each hospital was compared with other hospital using T-Test. The perception of clerkship students to preceptor was describe with likert scale and narrative description. Result: Students have independently faced 14 cases out of a total of 33 cases found in the manual of more than 50% of the 46 respondents. More than 50% of students agree with the supervisors teaching method. There is a significant difference of core case exposure between Blambangan Hospital and two other hospitals.Conclusions: Student’s exposure to the core case of surgical sciences is still low among the teaching hospital. Kanjuruhan Hospital has the lowest case exposure compared with other hospitals and has significant differences. Students' perceptions of preceptor are good enough and need to be improved.Keywords: Medical student, clinical competence, preceptor, teaching hospitals, department of surgery